+0  
 
0
174
1
avatar+177 

Geometry

party.girl286  Jan 29, 2018
 #1
avatar+89775 
+1

The diagonals of a parallelogram bisect each other

 

So this implies that 

 

DH  =  HF        and   GH  = HE

 

So

 

x + 3  =  3y      rearrange as    x  -  3y  =  - 3     (1)

4x - 5  = 2y + 3 rearrange as    4x - 2y  = 8  ⇒   2x  - y  =  4   (2)

 

 

Multiply (1)  by  -2  and we have that

 

-2x + 6y = 6          add this to  (2)  and we get that

 

5y  = 10   divide both sides by 2

y  = 2 

 

And using (1)

 

x - 3(2) =  - 3

x - 6  =  -3      add 6 to both sides

 

x =  3

 

So   {x, y}   =   {3, 2)  

 

 

 

cool cool cool

CPhill  Jan 29, 2018

11 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.